TAX BUILDS BEAUTY - Syafiqo Naila (22682490) (2025)
Taxes are the quiet force behind a nation’s glow-up. Every contribution helps transform ordinary spaces into cleaner streets, safer cities, and public facilities that actually feel good to use. When people participate, a country becomes more than functional it becomes a place that’s beautiful, livable, and worth calling home.